THE EFFECT OF VIRTUAL EDUCATION TO IMPROVE COMPLIANCE OF HEMODIALISYS PATIENTS WITH HEALTH PROTOCOLS DURING PANDEMIC - Nur Hidayati; Abdul Rokhman; Suratmi Suratmi; M. Syukri Ghozali; Muhtadi Muhtadi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: The spread of COVID-19 has continued to increase since March 2020. Patients with chronic kidney failure who undergo Hemodialysis are one of the groups vulnerable to COVID-19 because they routinely undergo Hemodialysis. One of the ways to prevent transmission of COVID-19 to hemodialysis patients is by providing education to comply with the COVID-19 prevention Health protocol. Objective: The purpose of this study was to determine the effect of virtual education on Hemodialysis patient compliance in preventing covid-19 transmission at the Muhammadiyah Hospital in Lamongan. Methods: This study used the Pre-Experiment approach one group pre-test post-test design on all CKD patients who were routine Hemodialysis at Muhammadiyah Lamongan Hospital from October - December 2020 who were taken using the purposive sampling technique. The intervention given was playing educational videos for 2 months. Data were collected using a questionnaire before and after the intervention, which was tested by the Wilcoxon test with α <0.05. Results: There were 69 patients who took part in the entire processes until it was completed. The results revealed that there were differences in the level of compliance of hemodialysis patients before and after treatment (p = 0.000). Further research with larger sample and RCT design is needed for stronger generalization in population. Conclusion: Providing educational videos can increase the level of compliance of hemodialysis patients in implementing Health protocols to prevent transmission of COVID-19.